2018
DOI: 10.1038/s41388-018-0602-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of p53-RBM25-mediated circAMOTL1L biogenesis contributes to prostate cancer progression through the circAMOTL1L-miR-193a-5p-Pcdha pathway

Abstract: p53, circRNAs and miRNAs are important components of the regulatory network that activates the EMT program in cancer metastasis. In prostate cancer (PCa), however, it has not been investigated whether and how p53 regulates EMT by circRNAs and miRNAs. Here we show that a Amotl1-derived circRNA, termed circAMOTL1L, is downregulated in human PCa, and that decreased circAMOTL1L facilitates PCa cell migration and invasion through downregulating E-cadherin and upregulating vimentin, thus leading to EMT and PCa progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
181
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 54 publications
2
181
0
Order By: Relevance
“…Recent studies have shown that circRNA functions through different actions, including serving as ‘miRNA sponge’, regulation of transcription and splicing, interacting with RNA‐binding protein, and even translating polypeptide . The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ‐HIPK3/miR‐7 in colorectal cancer, circ‐EPSTI1/miR‐942 in ovarian cancer, circ‐ANKS1B/miR‐148/152 in breast cancer and circ‐AMOTL1L/miR‐193a‐5p in prostate cancer . It is well recognized that miRNA is a post‐transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′‐UTR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that circRNA functions through different actions, including serving as ‘miRNA sponge’, regulation of transcription and splicing, interacting with RNA‐binding protein, and even translating polypeptide . The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ‐HIPK3/miR‐7 in colorectal cancer, circ‐EPSTI1/miR‐942 in ovarian cancer, circ‐ANKS1B/miR‐148/152 in breast cancer and circ‐AMOTL1L/miR‐193a‐5p in prostate cancer . It is well recognized that miRNA is a post‐transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′‐UTR .…”
Section: Discussionmentioning
confidence: 99%
“…16 The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ-HIPK3/miR-7 in colorectal cancer, 17 circ-EPSTI1/miR-942 in ovarian cancer, 18 circ-ANKS1B/ miR-148/152 in breast cancer 19 and circ-AMOTL1L/miR-193a-5p in prostate cancer. 20 It is well recognized that miRNA is a post-transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′-UTR. 21 In the current study, we identified that circ-CCND1 could simultaneously sponge three miR-646 to diminish the repression of miR-646 on CCND1 3′-UTR, resulting in enhancing the stability of CCND1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other similar reports in the study of PCa. Yang et al (2019) demonstrated that circAMOTL1L was a sponge that bound miR‐193a‐5p in PCa cells, alleviating the inhibition of miR‐193a‐5p on the Pcdha gene cluster and thus reducing PCa cell invasion and migration by upregulating vimentin and downregulating E‐cadherin. Chen et al (2019) indicated that circAGO2 plays an oncogenic role and promotes tumour progression by enhancing the inhibitory effect of human antigen R (HuR) on AGO2‐miRNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…While, as described above, linear ANRIL affects p53 stability via ARF [141], circANRIL expression impairs rRNA processing and maturation, ultimately leading to nucleolar stress and p53 activation [170]. The activation of p53 is also affected by other circRNAs, including: i) circ_0000263, which sponges miR-150-5p, in turn causing the up-regulation of the p53 inhibitor MDM4 [171]; ii) circ_0055538, whose loss in oral squamous cell carcinoma attenuates p53's pro-apoptotic response [172]; and iii) circAMOTL1L, whose downregulation promotes prostate cancer progression by impairing the p53dependent regulation of EMT [173]. Despite the numerous reports demonstrating the functional interactions between circRNAs and the p53 pathway (Table 3), further efforts are still needed to show whether circRNAs can also affect the stability or the activity of the remaining members of the p53 family and what consequences this interplay may have in human cancers and other biological processes.…”
Section: Circular Rnas and Their Effects On The P53 Pathwaymentioning
confidence: 99%
“…[171] circ_0055538 tumour suppressor required for p53-dependent apoptosis [172] circAMOTL1L tumour suppressor mediating p53 suppression of EMT [173] circANRIL causes p53 activation via nucleolar stress [170] PINT p53 target encoding a small tumour suppressive peptide [169]…”
Section: Marco Napolimentioning
confidence: 99%